2012
DOI: 10.1097/brs.0b013e31824a8314
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Ambulatory Performance and Self-Rated Disability in Patients With Lumbar Spinal Stenosis

Abstract: Subjective measures of pain and disability had limited ability to account for real-life performance in patients with LSS. Future research is required to identify determinants of performance in patients with LSS because barriers to activity may not be disease-specific.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 38 publications
1
33
0
Order By: Relevance
“…Nachemson showed that the percentage of the work force affected varied from 2% to 8% with days of absence from work per patient per year ranging from 9 days in the USA, to 10 days in West Germany, 20 days in Canada and Great Britain, and 25 days in the Netherlands, and 40 days in Sweden. It is estimated that 28% of the US industrial population will experience disabling low back pain at some time and that 8% of the entire working population will be disabled in any given year, contributing to 40% of all lost work days . State‐by‐state surveys in the USA show that occupational low back pain constitutes 9% to 26% of all industry insurance claims .…”
Section: Prevalencementioning
confidence: 99%
See 1 more Smart Citation
“…Nachemson showed that the percentage of the work force affected varied from 2% to 8% with days of absence from work per patient per year ranging from 9 days in the USA, to 10 days in West Germany, 20 days in Canada and Great Britain, and 25 days in the Netherlands, and 40 days in Sweden. It is estimated that 28% of the US industrial population will experience disabling low back pain at some time and that 8% of the entire working population will be disabled in any given year, contributing to 40% of all lost work days . State‐by‐state surveys in the USA show that occupational low back pain constitutes 9% to 26% of all industry insurance claims .…”
Section: Prevalencementioning
confidence: 99%
“…Consequently, low back pain remains one of the most controversial and difficult conditions to manage for clinicians, patients, and policy makers. Although low back pain is highly prevalent and invades all walks of life, the consequences are especially grave for the elderly .…”
Section: Introductionmentioning
confidence: 99%
“…These symptoms greatly interfere with an individual's ability to take part in normal work and recreational activities. 1 The interfer ence caused by these symptoms leads to reduced productivity and social participation that, in turn, leads to a diminished quality of life. 2 Lumbar spinal stenosis is often associated with neurogenic claudication, a condition that is made worse through physical activity, and is associated with lower limb numbness, weak ness, and pain.3 These symptoms often lead to reduced ambu lation and lower back pain.…”
mentioning
confidence: 99%
“…Survey measures tend to be the most popular method of measurement of function due to cost and ease of administration. Unfortunately, there is inconsistent support for the reliability and validity of surveys, and survey results frequently overestimate activity (Fitzhugh, 2015;Pryce et al, 2012). Challenges to self-report, particularly among older adults, include recall issues and bias due to social desirability (Sallis & Saelens, 2000;Sjostrom, 2002;Tooze et al, 2004).…”
Section: Introductionmentioning
confidence: 99%